2011
DOI: 10.4028/www.scientific.net/amr.399-401.474
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Jute Fibers Reinforced Friction Materials

Abstract: Jute fibers reinforced friction materials were prepared by mold and heat treatment. The friction coefficients of 3wt.%,9wt.% and 12wt.% jute fibers reinforced friction materials were bigger than that of the materials without jute fibers in the heating condition. The friction coefficient of 6 wt.% jute fibers reinforced friction materials was bigger than that of the materials without jute fibers below 250°C. The friction coefficient of jute fibers reinforced friction materials deceased with the temperature decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the treated composites with 3‐amino propyl trimethoxy silane and the trimethoxy methyl silane had higher thermal stability compared with that of untreated composites; and jute fiber composite treated by trimethoxy methyl silane, which had better fiber substrate adhesion, exhibited maximum abrasive wear resistance. Ma et al investigated the effect of jute fibers contents on the friction and wear properties of the friction materials. They indicated that the friction coefficients of friction materials reinforced with jute fibers of 3 wt %, 6 wt %, 9 wt %, and 12 wt % decreased with the decrease in temperature in cooling condition.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the treated composites with 3‐amino propyl trimethoxy silane and the trimethoxy methyl silane had higher thermal stability compared with that of untreated composites; and jute fiber composite treated by trimethoxy methyl silane, which had better fiber substrate adhesion, exhibited maximum abrasive wear resistance. Ma et al investigated the effect of jute fibers contents on the friction and wear properties of the friction materials. They indicated that the friction coefficients of friction materials reinforced with jute fibers of 3 wt %, 6 wt %, 9 wt %, and 12 wt % decreased with the decrease in temperature in cooling condition.…”
Section: Introductionmentioning
confidence: 99%
“…It could be inferred that the incorporation of PEEK fiber can reduce the sum of SWR by 13.51%–52.86% and PFS-6 had the optimal wear resistance. Furthermore, the wear resistance of RBFMs strengthened by PEEK fiber was higher than that of RBFMs strengthened by glass fiber [ 39 ], jute fiber [ 40 ] and corn stalk fiber [ 21 ].…”
Section: Resultsmentioning
confidence: 99%